Fly ash-GBBS blended geopolymer mortar for early engineering characteristic at ambient temperature - Nadarajah, Archanaah; Mohd Nasir, Noor Azline; Abu Bakar, Nabilah; Safiee, Nor Azizi (Ain Shams University, 2024)
Geopolymer concept is by using industrial waste materials which is rich in silica and alumina, then activating them with alkaline solution. An appropriate binder combination that achieves high early age strength at ambient temperature using FA is still subject required. Thus, this study has been designed in two stages which involving the paste and mortar studies. The alkaline activator as a blend of sodium hydroxide and sodium silicate solution with SS/SH ratio of 2.5, NaOH molarity of 12 M and L/B ratio of 0.43 are used for geopolymer composite. Compressive strength, water absorption and shrinkage are tested on geopolymer mortar with various level of blended combination. High volume content (60–80 %) gave a promising early age compressive strength at ambient temperature. Metakaolin gave a further strength improvement on geopolymer mortar. Overall, the finding suggested that the geopolymer with high FA content is suitable for cement-based material repair product.